Implementation Analysis Safety Culture to Improve the Quality of Health Services - Zulfa Nurul Fath; Dasrun Hidayat; Didin Syarifuddin (Research of Service Administration Health and Sains Healthys, 2025)
This study aims to analyze the implementation of patient safety culture at Kimia Farma Kosambi Karawang Clinic using a mixed methods approach with a sequential exploratory design. The research is motivated by the importance of safety culture as an indicator of healthcare service quality, especially considering the continued occurrence of incidents such as patient falls and the use of non- sterile equipment. The qualitative method involved in-depth interviews and observations of medical staff and management, while the quantitative method used a questionnaire based on 12 dimensions from AHRQ and was analyzed using SPSS. The findings show that active involvement of management, compliance of healthcare workers, and effective communication significantly contribute to the development of a strong safety culture. Identified barriers include low incident reporting, limited regular training, and weak inter-team collaboration. Recommended strategies include strengthening transformational leadership, implementing a non-punitive reporting system, SBAR communication training, and integrating local values into the organizational culture. The study concludes that the success of safety culture implementation highly depends on collaboration between management and healthcare workers in building a safe, adaptive, and sustainable service system, while also offering theoretical and practical contributions to the development of safety culture in primary healthcare settings.